2020
DOI: 10.1021/acs.nanolett.0c02898
|View full text |Cite
|
Sign up to set email alerts
|

Radio Waveguide–Double Ratchet Rotors Work in Unison on a Surface to Convert Heat into Power

Abstract: Synchronizing thousands of 100% efficient rotors in a macrodevice for harvesting noise is unapprehended. Thermodynamically, realizing a thermal gradient at the atomic scale is critical. Harvesting free thermal energy or noise by resonance has a hidden clause; either externally activating a directed self-powered motion or constructing a nanoscale power supply. To accomplish this, we combined two rotor concepts, Brownian rotor, BR, and power stroke, PS, rotors available in living systems in two planes of a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…We previously described the technique for actuating several DRMs in unison using radio waves. 9,56 The experiment showed that ac signals pumping on a DRM assembly anchored on the HOPG surface could generate useful power. 9,57,58 However, the difficulty lies in managing the rotational speed of the motor.…”
Section: Power Stroke (Ps) and Brownian Rotor (Br) Fusionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously described the technique for actuating several DRMs in unison using radio waves. 9,56 The experiment showed that ac signals pumping on a DRM assembly anchored on the HOPG surface could generate useful power. 9,57,58 However, the difficulty lies in managing the rotational speed of the motor.…”
Section: Power Stroke (Ps) and Brownian Rotor (Br) Fusionmentioning
confidence: 99%
“…9,56 The experiment showed that ac signals pumping on a DRM assembly anchored on the HOPG surface could generate useful power. 9,57,58 However, the difficulty lies in managing the rotational speed of the motor. We must thus look into whether such a constraint on rotation is built into the molecular orbitals and how the VIFC affects such a controlled rotation.…”
Section: Power Stroke (Ps) and Brownian Rotor (Br) Fusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ligands play several roles, e.g., as a light harvesting antenna, bridging the cationic nodes as linkers, creating supramolecular voids, conducting electrons and holes and finally, tuning bandgaps in the crystal lattice. If the ligand has a property of molecular motor and harvest energy to change the redox state of the metal center, then the result in a catalyst could be multipurpose, as by using their change of redox state the same catalyst structures can promote one or more parallel reactions sequentially or simultaneously in the same beaker [20]. Thus, it is possible to create many more time crystals, which may reduce the reaction time and cost.…”
Section: Designing Ligandsmentioning
confidence: 99%